Photo taken during the War Resisters' International 12th Conference at Rome. From: Vredesactie, Radicaal-pacifistisch maandblad, 1966, no. 6-7
Photo taken during the War Resisters' International 12th Conference at Rome. From: Vredesactie, Radicaal-pacifistisch maandblad, 1966, no. 6-7.